2011
DOI: 10.1002/clen.201000332
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Growth of Spirulina platensis and Removal of Hardness in Van Lake Water

Abstract: In this study, batch experiments were carried out to investigate simultaneous growth of Spirulina platensis and removal of hardness in the Van Lake Water (VLW). Laboratoryscale studies showed ample Spirulina growth observed in VLW when exposed to light. Spirulina was the only algal specimen inoculated in the water during the study. VLW percentages were varied between 0.1 and 100% while pH values were 8.7-10.42 in the flasks. On a dry-weight basis the biomass concentration was 1.18 g L À1 at pH 10 after 17 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Algal strains like Spirulina have been investigated for its potential as a bioremediation agent, although little information is available to support its use for bioremoval of heavy metals . Several researchers reported that Spirulina strains contain a variety of functional groups such as carboxyl, hydroxyl, sulfate, and other charged groups which are responsible for metal binding and thus these strains are useful for low cost industrial wastewater treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Algal strains like Spirulina have been investigated for its potential as a bioremediation agent, although little information is available to support its use for bioremoval of heavy metals . Several researchers reported that Spirulina strains contain a variety of functional groups such as carboxyl, hydroxyl, sulfate, and other charged groups which are responsible for metal binding and thus these strains are useful for low cost industrial wastewater treatment .…”
Section: Introductionmentioning
confidence: 99%
“…A. platensis is a source of high levels of proteins , polyunsaturated fatty acids (γ‐linoleic acid) , and pigments such as chlorophyll‐a . It can be used for environmental bioremediation as well as for a sustainable process of reusing its spent culture medium for new cultivations in batch or continuous processes . Furthermore, A. platensis biomass can be used as energy source .…”
Section: Introductionmentioning
confidence: 99%